EPISTEMIC CONTESTATION IN DETERMINING THE POSITION OF THE SUN DURING FAJR IN INDONESIA - Musonnif, Ahmad (UIN Sayyid Ali Rahmatullah Tulungagung, 2022)
Epistemic contestation in determining the position of the sun at fajr (dawn) in Indonesia occurred between Muhammadiyah and the Ministry of Religion as government representatives supported by Nahdlatul Ulama. This contestation pattern is in the form of a correction by Muhammadiyah to morning twilight criteria set by the Ministry of Religion. The government stipulated that the height of the sun at dawn is -20o while Muhammadiyah stated that the height of the sun should be 18o. Muhammadiyah's correction was based on research by the Muhammadiyah research team. Then the Ministry of Religion formed a research team that found that the sun's height at dawn is -20o. The Muhammadiyah research team falsified the findings of the Ministry of Religion team because the data is considered manipulative. The Ministry of Religion then responded with follow-up research elsewhere. Nahdlatul Ulama took part in this contest by forming a research team whose results contradicted the results of the Muhammadiyah yet strengthened the Ministry of Religion's decision regarding the morning twilight criteria. The contestation does not lead to an epistemic meeting point. Although both parties used the same method, namely empirical observations in the field, the pre-assumptions at the time of the research led to different conclusions.